Potencial pesticida da erva-de-santa-maria (Chenopodium ambosioides): uma revisão sistemática da literatura - Damasceno, Nathalia de Sousa (2021)
Agriculture in Brazil is going through a trajectory of advances. Although there are several positive points for the advancement of Brazilian agriculture, there are still issues to be overcome, such as the impact on the environment and health. Brazil is considered worldwide as one of the main users of agrochemicals. It is a worrying fact, since the chronic ingestion of these products leads to relevant pathologies, such as malignant tumors, neurotoxic action, pulmonary fibrosis, corrosive action on mucous membranes, asthma attacks, eye irritation, among others. Because of these challenges in the management of pesticides, much research has now been invested in natural pesticides. This study aims to conduct a systematic review of the literature on experimental studies that have tested the pesticide potential of Erva-de-Santa-Maria (Chenopodium ambrosioides) against agricultural pests. 23 articles on the use of Erva-de-Santa-Maria as a potential pesticide were analyzed. Of the 23 studies, it was observed that they differed as to the methodology used for the experiment, using three forms of active ingredients: essential oil, vegetable powder and vegetable extract. Thus, seven studies addressed the use of Erva-de-Santa-Maria in the form of essential oil, nine used plant extract, six in the form of vegetable powder and one tried two active principles concomitantly, that of vegetable powder and plant extract. During the analysis of the articles, what most sparked discussions were the discrepancies found between the studies. The same active principle was not similar in several outcomes, this leads us to think about the methodologies used to test the active principles. These discrepancies could be mitigated if there was a standardization as to the experiments carried out. Be it in the concentration of the substances, the methods of obtaining the active principles, in the standardization of the control groups (witness), even in the days of analysis of the experiments